(untitled) (Scientific journal of the Fergana State University, 2026)
Currently, due to the impact of unfavorable socialization conditions, the number of adolescents exhibiting deviant victimization has increased. One of the key contributing factors to the development of deviant victimization is family dysfunction. This article explores the indicators of personal victimization and the main factors influencing adolescent victimization, including asocial family environments, domestic violence, criminal surroundings, and the absence of a safe educational setting. Evidence-based conclusions suggest that adverse socialization conditions significantly heighten the risk of deviant victimization among adolescents. The findings highlight the urgent need for timely psychological and pedagogical support for both the family and the adolescent, as well as the integration of efforts by all stakeholders —society, the state, and educational institutions.